Manipulation in Interpellation of Iraqi Parliamentary Discourse - Addai Al Ghezzey, Khalida Hashoosh (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The purpose of this study is to analyze the language of parliamentary discourse and in particular interpellations. These interpellations are forwarded by an MP- usually affiliated to an opposition party- to the speaker, who in turn decides on the adequacy and sufficiency of the evidences provided to justify an interpellation. The interpellator then presents his argument, and in the same session the Minister is invited to answer to the allegations. It focuses on the discourse of both MPs and Ministers looking at the strategies employed by both parties to persuade and convince those who are listening to the proceedings.